Sprays and lozenges for sore throats - F. Farrer (South African Family Practice, 2012)
A sore throat is a common complaint, and often an early indication of another medical condition, such as a cold. In the absence of life-threatening conditions or bacterial infection, local symptomatic treatment will ease the pain. This article reviews the common causes and symptoms of sore throats, and provides an overview of some of the sprays and lozenges that are available to treat this problem.